Foodie snob - Nelson, Kevin (Lyons Press, 2017)
Food-lovers will enjoy this fun and lighthearted look at their obsession with trendy food and restaurants. Food Snob is both be a send-up of foodies and an affirmation of certain aspects of the foodie way of life. While laughing at this satire of the habits, attitudes and lifestyle of foodies, foodies will laugh at themselves and also get solid advice and tips on the activity they love